Intervensi Keperawatan Gizi pada Pekerja Shift Malam Minimarket Alfamart di Kota Makassar - Asrar As; Asmiana Saputri Ilyas; Ma’rifat Istiqa Mukty; Zulfitrawati Zulfitrawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Night shift workers in the modern retail sector, especially minimarkets such as Alfamart Makassar City, often face the risk of health problems due to changes in circadian rhythms, irregular diets, and lack of nutrition education. Work patterns that require them to be active at night have an impact on metabolic imbalances, sleep quality disorders, and unhealthy eating habits. Most workers tend to eat fast food that is high in calories, fat, and sugar, but low in fiber and micronutrients. This condition can increase the risk of fatigue, decreased immunity, and impaired concentration at work. This study aims to evaluate the effectiveness of nutritional nursing interventions in improving the diet and physical condition of night shift workers. The research approach used was descriptive with a case study method on 32 Alfamart workers who worked night shifts. The research was carried out for three days, namely on May 24-26, 2025. The interventions provided include nutrition education through brief counseling, monitoring of food and fluid intake, and assistance in developing a meal schedule that is in accordance with night work patterns. The results of the study showed a significant improvement in nutritional behavior. After the intervention, 84% of participants started implementing a healthy diet with a frequency of twice per shift, 93% increased their water consumption as recommended, and 72% felt refreshed and did not get tired easily while working. In addition, as many as 78% of participants showed high compliance with the nutritional recommendations given. These findings prove that nutritional nursing interventions have an important role in the promotion of occupational health. Proper nutrition education not only increases workers' awareness of the importance of a healthy diet, but also has an impact on increasing the productivity and welfare of night shift workers. Therefore, nutrition promotion programs should be part of the management policies of retail companies to maintain employee health.